2018
DOI: 10.1371/journal.pone.0191622
|View full text |Cite
|
Sign up to set email alerts
|

Comparing autotransporter β-domain configurations for their capacity to secrete heterologous proteins to the cell surface

Abstract: Monomeric autotransporters have been extensively used for export of recombinant proteins to the cell surface of Gram-negative bacteria. A bottleneck in the biosynthesis of such constructs is the passage of the outer membrane, which is facilitated by the β-domain at the C terminus of an autotransporter in conjunction with the Bam complex in the outer membrane. We have evaluated eight β-domain constructs for their capacity to secrete fused proteins to the cell surface. These constructs derive from the monomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
(171 reference statements)
1
18
0
Order By: Relevance
“…A panel of cell surface scaffold modules were chosen based on their ability to direct passenger proteins to the E. coli outer membrane. These included cytolysin ClyA (18), hybrid protein Lpp-OmpA (35), and the autotransporter β -domains derived from the N-terminus of intimin (Int) (36) and the C-termini of adhesin involved in diffuse adherence (AIDA-I), antigen-43 (Ag43), hemoglobin-binding protease (Hbp), and immunoglobulin A protease (IgAP) (37).…”
Section: Resultsmentioning
confidence: 99%
“…A panel of cell surface scaffold modules were chosen based on their ability to direct passenger proteins to the E. coli outer membrane. These included cytolysin ClyA (18), hybrid protein Lpp-OmpA (35), and the autotransporter β -domains derived from the N-terminus of intimin (Int) (36) and the C-termini of adhesin involved in diffuse adherence (AIDA-I), antigen-43 (Ag43), hemoglobin-binding protease (Hbp), and immunoglobulin A protease (IgAP) (37).…”
Section: Resultsmentioning
confidence: 99%
“…In earlier studies, we have reported on the limited tolerance of Hbp to transport folded heterologous protein domains across the outer membrane where such DTS constructs showed a decreased secretion efficiency when compared to wild-type Hbp or efficiently-secreted derivatives [ 13 , 16 , 41 ]. Examples of DTS inserts are the calmodulin domain that forms a stable fold in the presence of calcium ions [ 16 ] and a single-chain antibody domain that includes two disulfide bonds [ 14 ]. To systematically investigate the limits of Hbp secretion, we previously constructed a DTS Hbp with an α-helical hairpin formed by two stable α-helices derived from ribosomal protein L9 of Bacillus stearothermophilus constricted into an hairpin through a disulfide bond formed between cysteine residues engineered at positions 707 and 712 of the Hbp passenger (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These small domains (15 kDa) are known to fold in the periplasm and include one disulphide bond. Fusing GFPnb to HbpD has been shown to impair expression and surface display [ 14 , 52 ]. We tested the effect of co-expression of BAM on expression and display of DTS HbpD-GFPnb cloned into pLEMO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various specific β-barrels of autotransporters have been shown to secrete recombinant proteins to the cell surface, but the transport efficiencies of different β-barrels are different. The Hbp passenger domain is often used as a transport target to evaluate the transport capacity of the β-barrels of autotransporters (Jong et al, 2018). To investigate whether the NGO2105 β-barrel can secrete the heterologous passenger domain, we fused a small Myc tag and Hbp passenger domain upstream of the β-barrel of NGO2105.…”
Section: Discussionmentioning
confidence: 99%